Optimizing Tip Diameter in Phacoemulsification of Varying Lens Sizes: An in vitro Study - Ramshekar A (Dove Medical Press, 2021)
Aniket Ramshekar,1,2 Joshua Heczko,1 Ashlie Bernhisel,1 William Barlow Jnr,1 Brian Zaugg,1 Randall Olson,1 Jeff Pettey1 1Department of Ophthalmology and Visual Sciences, John A. Moran Eye Center, University of Utah, Salt Lake City, UT, 84132, USA; 2University of Utah School of Medicine, Salt Lake City, UT, 84132, USACorrespondence: Jeff PetteyDepartment of Ophthalmology and Visual Sciences, John A. Moran Eye Center, University of Utah, 65 Mario Capecchi Drive, Salt Lake City, UT, 84132, USATel +1 801-581-2352Fax +1 801-581-3357Email jeff.pettey@hsc.utah.eduPurpose: We assessed the effect of two lens cube sizes, three tip sizes, and two ultrasound (US) approaches on phacoemulsification efficiency and chatter.Methods: After porcine lens nuclei were soaked in formalin, we divided them into cubes measuring 2.0 mm or 3.0 mm. We collected efficiency and chatter data for 30-degree bent 19 G, 20 G, and 21 G tips with a continuous torsional US system; and for straight 19 G, 20 G, and 21 G tips with a micropulse longitudinal US system.Results: The average time needed for removal was always higher for the 3.0 mm lens cube than for the 2.0 mm lens cube. Statistically significant differences were observed between the 19 G and 21 G tips with micropulse longitudinal US using a 2.0 mm cube and a 3.0 mm cube, and with continuous transversal US using a 2.0 mm lens cube and a 3.0 mm cube. We did not observe significant differences between 19 G and 20 G tips with either cube size in either US system. However, we noted identical trends for both cube sizes with both US approaches; 19 G tips performed better than 20 G and 21 G tips.Conclusion: Regardless of the lens size, 19 G needles were the most efficient, and had both the fewest outliers and the smallest standard deviations.Keywords: cataract, chatter, efficiency, tip diameter, vacuum